Declared use of medication in sports - van Thuyne, W.; Delbeke, F. T. (Clinical Journal of Sport Medicine, 2008)
Objective: To assess and compare the prevalence of declared medication, such as corticosteroids, nonsteroidal anti-inflammatory drugs (NSAIDs), [beta]2-agonists, narcotic analgesics, anaesthetics, and antidepressant drugs, in time and between different sports among athletes tested for doping control in a 4-year period.